Image Categorization using Color Blobs in a Mobile Environment - Gavilan Ruiz, David; Takahashi, Hiroki; Nakajima, Masayuki (Computer Graphics Forum (EG 2003), 2003)
This paper generalizes the basic idea of blobs in preattentive perception using color information. This is usedas the base of a basic classification of low resolution pictures taken with mobile phones. This classification, theblob‐like representation of the image and other information in user's context, such as GPS information, can beused in the presented framework as the basis of a new graphical interface for HCI (Human Computer Interaction).Similar systems whether they work with global properties of the image, which leads to inaccurate results, or withcomplex segmentation process that fails to capture expected objects in the scene. Most of those systems do notpay attention on other information involved in the creation of the image, such as time or location. We describe asystem which uses geographical information associated with a picture in a mobile phone terminal, and with a fastsegmentation based on color categorization.